Short-term effects of the prestige oil spill on the peregrine falcon (Falco peregrinus) - Zuberogoitia, Íñigo; Martínez, José Antonio; Iraeta, Agurtzane; Azkona, Ainara; Zabala, Jabi; Jiménez, Begoña; Merino, Rubén; Gómez, María Gema (Marine Pollution Bulletin, 2006)
6 pages.-- Original working paper (extended-version in Spanish) available at Digital.CSIC: http://digital.csic.es/handle/10261/6808.-- Final full-text version of the paper available at: http://dx.doi.org/10.1016/j.marpolbul.2006.02.016. We have monitored the distribution, population status, breeding success, turnover rate and diet of a Peregrine Falcon population in Bizkaia (North of Spain) since 1997. On the 13th November 2002, the tanker Prestige sunk off La Coruña (NW Spain) causing an oil spill that affected the whole of the Cantabrian Coast and the Southwest of France. The total number of birds affected by the Prestige oil spill was expected to be between 115,000 and 230,000, some of them raptors. The loss of clutches during the incubation period increased significantly and was correlated with the loss of females. Moreover, the turnover rate of the population increased from 21% to 30%. The polycyclic aromatic hydrocarbon concentrations in the eggs, collected from five nests after they were deserted, ranged from 21.20 ng/g to 461.08 ng/g, values which are high enough to cause the death of the embryos and poisoning of adult birds. The effects of pollution reached inland since some inland-breeding falcons prey on shorebirds that use rivers during their migratory flights. As the Prestige oil spill has clearly resulted in increased rates of adult mortality and reduced fertility, we suggest that the environmental authorities urgently undertake measures aimed at protecting the Peregrine Falcon in Bizkaia. The Biodiversity Department of Basque Government partially supported this study. The Dpto Agricultura, Diputación Foral de Bizkaia, provided the licences to work with Peregrine Falcons and the San Sebastian Ringing Scheme contributed with the material for ringing. Peer reviewed